(untitled) (European Journal of Formal Sciences and Engineering, 2021)
Nowadays there are growing interests in vibration serviceability assessments of composite footbridges. The new design trends of composite footbridges make them slender civil structures that may be affected by the load action of walking pedestrians resulting in large deflections or even uncomfortable vibrations. Furthermore, the presence of people on the footbridges causes the addition of mass to the structural system and due to the human body’s ability to absorb vibrational energy, an increase in structural damping. In this paper, the interaction between pedestrian and structure is modelled using data from pedestrian characteristics and vibration data from a measured footbridge as a comparison basis. A previously developed numerical model was used, this model called Biodynamic Synchronized Coupled Model (BSCM) consists of a fully synchronized force model in the longitudinal and lateral direction of pedestrian’s movement and a biodynamic model with mass, damping and stiffness parameters. The model is coupled with the structure using the Finite Element Method at the feet’s contact points. Pedestrians are treated as individuals with intrinsic kinetic and kinematic parameters following a measured correlation matrix obtained by the use of an especially designed force platform. Finally, the adequacy of the proposed model to represent the pedestrians as BSCM for the walking effects on the structure is investigated by experimentally measured accelerations on a footbridge (freely walking). The numerical results show good agreement with the experimental results.